2012
DOI: 10.1093/nar/gks265
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between DNA, transcriptional regulator Dreb2a and the Med25 mediator subunit from Arabidopsis thaliana involve conformational changes

Abstract: Mediator is a multiprotein coregulatory complex that conveys signals from DNA-bound transcriptional regulators to the RNA polymerase II transcription machinery in eukaryotes. The molecular mechanisms for how these signals are transmitted are still elusive. By using purified transcription factor Dreb2a, mediator subunit Med25 from Arabidopsis thaliana, and a combination of biochemical and biophysical methods, we show that binding of Dreb2a to its canonical DNA sequence leads to an increase in secondary structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…Subsequent research on DREB2A-INTERACTING PROTEIN1 and DRIP2 revealed their roles in the rapid degradation of DREB2A through 26S proteasome-dependent proteolysis under nonstress conditions (Qin et al, 2008). Recently, reports on Arabidopsis MEDIATOR25, a newly described DREB2A-interacting cofactor protein, suggested another method of regulation of DREB2A activation (Elfving et al, 2011;Blumberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research on DREB2A-INTERACTING PROTEIN1 and DRIP2 revealed their roles in the rapid degradation of DREB2A through 26S proteasome-dependent proteolysis under nonstress conditions (Qin et al, 2008). Recently, reports on Arabidopsis MEDIATOR25, a newly described DREB2A-interacting cofactor protein, suggested another method of regulation of DREB2A activation (Elfving et al, 2011;Blumberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These changes, combined with other signal pathways that cause posttranslational modifications of different transcription factors, might therefore determine the level of transcription from each gene (Blomberg et al, 2012). Consistent with this idea, Blomberg and colleagues have found that binding of DREB2A to its canonical DNA sequence leads to an increase in secondary structure of the transcription factor.…”
Section: Interaction Of Med25mentioning
confidence: 87%
“…Surprisingly, Blomberg et al (2012) demonstrated that DREB2A from Arabidopsis can interact with the human MED25 ACID domain and displayed similar complex kinetics as the Arabidopsis MED25 ACID domain with DREB2A interaction. This result not only suggests that there is sequence similarity in the ACID domain between the two species, but also it proposes that whatever is discovered in plant gene regulation through the Mediators complex may be applied to the human Mediator complex.…”
Section: Interaction Of Med25mentioning
confidence: 99%
See 2 more Smart Citations